Promoting health and quality of life of patients with osteoarthritis of knee joint through non-pharmacological treatment strategies: A randomized controlled trial - Nirav Vaghela; Daxa Mishra; Jayshree Patel; Vyoma Dani (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND OBJECTIVE: Osteoarthritis (OA) is a chronic degenerative disorder which primarily affects the articular cartilage of synovial joints followed by bony remodeling and overgrowth at the margins of these joints. The consequences of OA are pain, joint stiffness, decreased muscle performance, and decreased aerobic capacity, which eventually affect the quality of life (QOL) and increased risk for disability. The objective of the present study was to investigate the effectiveness of two nonpharmacological treatment regimens, that is, yoga and conventional physiotherapy, on QOL in patients suffering from OA of knee joint. MATERIALS AND METHODS: A total of 83 patients with bilateral OA of knee joint, between the age group of 40 and 80 years, both males and females, were assigned into two groups using computer-generated scheme: 43 in the experimental group (yoga with conventional physiotherapy program) and 40 in control group (conventional physiotherapy program). Western Ontario and McMaster Universities OA index (WOMAC) and Short-Form 36 (SF-36) health survey were measured before, after 15 days, and after 30 days of treatment sessions, and the data were analyzed using paired and unpaired t-test. RESULTS: The results of the study show significant improvement in both groups with regard to WOMAC and SF-36 at the end of 15 and 30 days of treatment regimen; however, when compared to the control group, experimental group had more significant improvement (P < 0.05) in WOMAC and SF-36 at the end of 15 and 30 days of treatment. CONCLUSION: Yoga is more beneficial when added to conventional physiotherapy treatment regimen in promoting health and improving QOL in patients with OA of knee joint.